Innovation at work: The relative advantage of using consumer IT in the workplace. (23rd March 2018) - Junglas, Iris; Goel, Lakshmi; Ives, Blake; Harris, Jeanne
Abstract: Employees' personal devices are increasingly evident in the workplace; the use of non‐enterprise sanctioned hardware and software is now commonplace. This phenomenon, frequently referred to as IT consumerization, is gaining momentum. Employees increasingly are using their own devices and choosing their own software (eg, Google Apps, Skype or Dropbox) in addition to—or instead of—enterprise IT. Employees are turning from consumers of enterprise IT to IT deciders, bypassing the IS department to use what critics call "rogue IT." While discouraged in some contexts, the influx of consumer IT into the workplace has been suggested to influence innovative behaviours among employees. Although the phenomenon is very prevalent, research lags in the operationalization of an IT consumerization model. In this paper, we take a close look at the antecedents and consequences of consumerization behaviours. We examine to what extent an individual's level of satisfaction with enterprise IT in juxtaposition with the level of perceived relative advantage of consumer IT over enterprise IT influences an individual's usage of consumer IT in the workplace; we also examine how organizational mandates and IT empowerment influences IT consumerization behaviours. Finally, we investigate the influence of IT consumerization on innovative behaviours at work.